Immune Thrombocytopenia in Two Unrelated Fanconi Anemia Patients – A Mere Coincidence? - Karastaneva, Anna; Lanz, Sofia; Wawer, Angela; Behrends, Uta; Schindler, Detlev; Dietrich, Ralf; Burdach, Stefan; Urban, Christian; Benesch, Martin; Seidel, Markus G. (Frontiers in Pediatrics, 2015)
Thrombocytopenia and pancytopenia, occurring in patients with Fanconi anemia (FA), are interpreted either as progression to bone marrow failure or as developing myelodysplasia. On the other hand, immune thrombocytopenia (ITP) represents an acquired and often self-limiting benign hematologic disorder, associated with peripheral, immune-mediated, platelet destruction requiring different management modalities than those used in congenital bone marrow failure syndromes, including FA. Here we describe the clinical course of two independent FA patients with atypical - namely immune - thrombocytopenia. While in one patient belonging to complementation group FA-A, the ITP started at 17 months of age and showed a chronically persisting course with severe purpura, responding well to intravenous immunoglobulins (IVIG) and later also danazol, a synthetic androgen, the other patient (of complementation group FA-D2) had a self-limiting course that resolved after one administration of IVIG. No cytogenetic aberrations or bone marrow abnormalities other than FA-typical mild dysplasia were detected. Our data show that acute and chronic ITP may occur in FA patients and impose individual diagnostic and therapeutic challenges in this rare congenital bone marrow failure / tumor predisposition syndrome. The management and a potential context of immune pathogenesis with the underlying marrow disorder are discussed.